A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae) - Alipanah, Helen; Baixeras, Joaquín (Zootaxa, 2011)
Hedya tritofa, new species, is described and illustrated based on eleven males and five females collected in northern Iran (Gilan, Mazandaran, and Golestan provinces). Morphology and diagnostic characters of Hedya Hübner, 1825, Metendothenia Diakonoff, 1973, the Olethreutes group of genera, and the Neopotamia group of genera are discussed. We propose the resurrection of the combinations Hedya atropunctana (Zetterstedt, 1840), revised status, and H. separatana (Kearfott, 1907), revised status, and the new combination H. inouei (Kawabe, 1987).